When women kill: questions of agency and subjectivity / Belinda Morrissey. - Morrissey, Belinda (Transformations : thinking through feminism., 2003)
Based on case studies from the US, UK and Australia, this text looks at the ways in which female killers are constructed in the media, in law and in feminist discourse almost invariably as victims rather than actors in the crimes they commit.